Microsurgical replantation after forehead avulsion - success or failure? A case report - Kubík, Marek; Molitor, Martin; Zálešák, Bohumil (Acta chirurgiae plasticae, 2024)
In this article we would like to present, to our best knowledge, the very first published replantation of a forehead/part of a forehead as a single unit. The patient is a 57-year-old male smoker who sustained an avulsion forehead injury after a dog bite. Replantation was performed using microanastomosis of the supratrochlear vessels with restoration of good blood circulation after the procedure. Unfortunately, 5 days after the surgery, ischemia of the flap occurred followed by successful acute revision surgery. Nevertheless, the day after the ischemia reoccurred due to the time that passed, circumstances and unfavorable conditions affecting the sutured vessels, no further revision surgery was indicated. Observation continued and eventual wound necrosis after demarcation was left to be treated with skin grafting or per secundam intentionem. Only partial necrosis of the flap occurred, approximately 50%, which was subsequently treated with a full-thickness skin graft with very good results leading to the satisfaction of the patient.
Keywords: replantace; skalpační poranění; mužské pohlaví; Male; Replantation; Humans; Degloving Injuries; cévy; Bites and Stings; recidiva; lidé; Middle Aged; lidé středního věku; Blood Vessels; nekróza; Forehead; čelo; kouření; Ischemia; anastomóza chirurgická; Necrosis; Smoking; ischemie; Recurrence; Anastomosis, Surgical; kousnutí a bodnutí; mikrochirurgie; Microsurgery